Application of non-enzymatic browning of fructose for heating pattern determination in microwave assisted thermal pasteurization system. (October 2017) - Jain, Deepali; Wang, Jungang; Liu, Frank; Tang, Juming; Bohnet, Stewart
Abstract: Various model foods and chemical markers have been used for the heating pattern determination in microwave processing at sterilization temperatures (110–130 °C). These chemical marker systems have slow reaction rates and are not useful at pasteurization temperatures (70–90 °C). In this study, non-enzymatic browning of fructose under alkaline conditions is investigated for its suitability to be used in the heating pattern determination for microwave assisted thermal pasteurization. Kinetics of browning of fructose in the mashed potato model food were studied. The model food samples were heated in a water bath at 60 °C, 70 °C, 80 °C and 90 °C for different time intervals and the browning kinetics were studied by spectrophotometric measurements at 420 nm. Reaction rate kinetics were fit to a linear first order kinetic model. Application of this model food to determine the heating pattern in the microwave assisted thermal pasteurization system was demonstrated. Dielectric properties of the mashed potato were measured to determine its suitability as a model food. Sucrose and salt were used as effective additives for the adjustment of the dielectric constants and loss factor respectively of the mashed potato. This system offers advantages of being cost-effective, opaque, homogeneous and easy to handle and thus provides an excellent system to locate the hot and cold spots of the food products. Highlights: Non-enzymatic browning of fructose was used as a time temperature indicator in microwave pasteurization. Dielectric properties of the model food were tailored to match the real foods. Locations of cold and hot spots were determined using computer vision method. Heating pattern was validated using temperature sensors.